Yield of emergent neuroimaging in children with new-onset seizure and status epilepticus. (February 2016) - Lyons, Todd W.; Johnson, Kara B.; Michelson, Kenneth A.; Nigrovic, Lise E.; Loddenkemper, Tobias; Prabhu, Sanjay P.; Kimia, Amir A.
Highlights: Retrospective cohort of children with new-onset seizure with status epilepticus. Evaluated yield of neuroimaging for urgent or emergent intracranial pathology. 8.5% of children found to have urgent or emergent intracranial pathology. 27% of urgent or emergent findings were not present on initial non-contrast CT scan and were not discovered until subsequent MRI. Abstract: Purpose: To determine the yield of emergent neuroimaging among children with new-onset seizures presenting with status epilepticus. Method: We performed a cross-sectional study of children seen at a single ED between 1995 and 2012 with new-onset seizure presenting with status epilepticus. We defined status epilepticus as a single seizure or multiple seizures without regaining consciousness lasting 30 min or longer. Our primary outcome was urgent or emergent intracranial pathology identified on neuroimaging. We categorized neuroimaging results as emergent if they would have changed acute management as assessed by a blinded neuroradiologist and neurologist. To ensure abnormalities were not missed, we review neuroimaging results for 30 days following the initial episode of SE. Results: We included 177 children presenting with new-onset seizure with status epilepticus, of whom 170 (96%) had neuroimaging performed. Abnormal findings were identified on neuroimaging in 64/177 (36%, 95% confidence interval 29–43%) children with 15 (8.5%, 95% confidence interval 5.2–14%) children having urgent or emergent pathology. Four (27%) of the 15 children with urgent or emergent findings had a normal non-contrast computed tomography scan and a subsequently abnormal magnetic resonance image. Longer seizure duration and older age were associated with urgent or emergent intracranial pathology. Conclusion: A substantial minority of children with new-onset seizures presenting with status epilepticus have urgent or emergent intracranial pathology identified on neuroimaging. Clinicians should strongly consider emergent neuroimaging in these children. Magnetic resonance imaging is the preferred imaging modality when available and safe.